Skin lesions as an initial manifestation of late osteosynthesis‐associated infection - Raúl Gutiérrez‐Meré; Ana Batalla; Juan Carlos Feal Cortizas; Gonzalo Peón‐Curras; Maria Teresa Abalde; Carlos Fernández Da Ponte García; Carmen Couselo‐Rodríguez; Diego Soto‐García; Sandra Martínez‐Fernández; Ángeles Flórez (Wiley, 2023)
Abstract Late osteosynthesis‐associated infection (OAI) is an uncommon and potentially serious disease. Its clinical presentation may mimic skin and soft tissue infection, leading to misdiagnosis. We report the case of a 64 year‐old man with a late OAI in the frontal bone, initially misdiagnosed as an infectious cellulitis. Late OAI can be difficult to suspect, especially if the intervention was performed years ago. Because of misdiagnosis, the symptoms can be masked by the use of antibiotics, so it is of utmost importance to take a detailed clinical history to make an early diagnosis and avoid potential complications. The treatment consists of the use of antibiotics and the replacement of the osteosynthesis material. Therefore, when facing a skin and soft tissue infection of torpid evolution which persists despite correct treatment and a past medical history of underlying osteosynthesis material, late OAI should be considered.